Isolation and Characterization of Coronavirus and Rotavirus Associated with Calves in Central Part of Oromia, Ethiopia - Umer Seid; Fufa Dawo; Asamino Tesfaye; Munera Ahmednur (Veterinary Medicine International, 2020)
Background. Coronavirus and rotavirus are most commonly associated etiologies for calves’ diarrhoea, resulting in loss of productivity and economy of farmers. However, various facets of diarrheal disease caused by coronavirus and rotavirus in calves in Ethiopia are inadequately understood. A cross-sectional study was conducted with the aim of isolation and molecular characterization of coronavirus and rotavirus from calves in the central part of Oromia (Bishoftu, Sebata, Holeta, and Addis Ababa), Ethiopia, from November 2018 to May 2019. The four study areas were purposively selected and faecal samples were collected by simple random sampling for diagnosis of coronavirus and rotavirus infection by using the antigen detection enzyme-linked immunosorbent assay (Ag-ELISA) kit. In addition, this study was carried out to have insight in prevalence and associated risk factors of coronavirus and rotavirus infection in calves. Result. During the study, 83 diarrheic and 162 nondiarrheic faecal samples collected from calves less than 4 weeks of age were screened for coronavirus and rotavirus. Of the 83 diarrheic samples, 1 sample (1.2%) was positive for coronavirus antigen and 6 samples (7.2%) were found to be positive for rotavirus antigen by Ag-ELISA. All the nondiarrheic samples were negative for both coronavirus and rotavirus Ag. The overall prevalence of coronavirus and rotavirus infection in calves was estimated at 0.4% (1/245) and 2.45% (6/245), respectively. All samples (7) of ELISA test positive of both coronavirus and rotavirus were propagated in Madin-Darby bovine kidney (MDBK) cells. After 3 subsequent passages, progressive cytopathic effect (CPE), i.e., rounding, detachment, and the destruction of monolayer cell of five samples (1 sample of coronavirus and 4 samples of rotavirus) (71.4%) were observed. At the molecular stage, reverse transcriptase polymerase chain reaction (RT-PCR) technique was used to determine the presence of coronavirus and rotavirus nucleic acid by using specific primers. The 5 samples that were coronavirus and rotavirus antigen positive by ELISA and develop CPE on cell culture were also positive on RT-PCR technique. The prevalence of infection peaked at 1st and 2nd weeks of age in male calves. Conclusion. Diarrheal disease caused by coronavirus and rotavirus has a great health problem in calves that interrupts production benefits with reduced weight gain and increased mortality and its potential for zoonotic spread. So, the present findings show coronavirus and rotavirus infection in calves in Ethiopia that needs to be addressed by practising early colostrum feeding in newborn calves, using vaccine, or improving livestock management.